A indústria de confecção do vestuário do município de Pato Branco: aspectos de desenvolvimento, gestão, design, e proposta de reaproveitamento dos resíduos têxteis - Mesacasa, Andréia (2012)
The industrial culture provided a number of benefits to modern society, however, negative environmental impacts have been generated as a function of inadequate exploration of the planet's natural resources and the excessive generation of waste. According to this context, this study has focused on the clothing apparel industry in Pato Branco city, and tries to reveal aspects of the management, design, characterization of raw materials and waste generation. Furthermore, in an attempt to alleviate the bottleneck regarding the correct disposal of waste generated in the textile production process, proposed as an alternative reuse of these through the development of fashion products aimed at the female audience, such as handbags and scarves. This study involved three distinct stages. The first one was composed of a diagnosis made with the companies in order to obtain information regarding the profiles of the same, highlighting the forms of management, design and product development, raw materials and generation of waste textiles. Such companies are characterized as small and micro enterprises, operating in different market segments, with a strong tendency to produce professional uniforms. As a result, much of the waste generated consists of scraps of fabric. It was evident shortage of qualified professionals to work both in areas of design, development and production, which in some ways an obstacle to the growth of businesses in the city. After that, in a second phase of the study was conducted with 200 potential consumers of fashion products in Pato Branco city, to verify the same preferences related to fashion, including aspects such as willingness to purchase products made from waste textiles and craft techniques such as knitting , crochet, embroidery, factors relevant to profile the consumers. Based on data collected were developed fashion products from waste textiles. Assuming that the launch of environmentally friendly products requires cultural and social acceptance by consumers, the third phase of the study was conducted evaluating the acceptance of fashion products, using, in an innovative fashion products, the methodology hedonic scale for sensory evaluation and testing of intent to purchase. We evaluated the technical attributes, ergonomic and aesthetic products. Products developed from waste textiles had good acceptance and purchase intent appreciable, demonstrating a high potential for reuse of the same technology. The reuse of waste could contribute to both the environmental point of view through better targeting of these, as economically as it could be directed to the production of higher added value.